Dermcidin has antiviral activity and protects against influenza - Paula Corell-Escuin; Sonia Belmonte-Ballester; Anmol Adhav; Alberto Marina; Laura Gadea-Salom; Luis Martinez-Gil; Elnaz Aledavood; Ana María Fernández-Escamilla; Ana Gómez Sáez; Nadine Gougeard; Kieran Dee; Pablo R. Murcia; et al. (Proceedings of the National Academy of Sciences, 2026)
Despite the high incidence of influenza virus infections, one-fifth of people infected with influenza remain asymptomatic. The mechanisms associated with this immune resilience are, however, unknown. Here, we show that the human antimicrobial peptide dermcidin has antiviral activity against influenza viruses through binding to hemagglutinin and extends its effect to taxonomically unrelated respiratory viruses such as measles virus and human coronavirus OC43. We show that dermcidin is present in all anatomical regions associated with the entry routes of respiratory viruses, that its levels increase during viral respiratory infections, and that it protects mice against influenza disease. Notably, dermcidin levels were higher in asymptomatic individuals than in susceptible peers, suggesting a role in the onset of disease symptoms. Thus, we show that dermcidin inhibits influenza virus infection in vitro and in vivo, with potential as a human-derived product for the prevention and treatment of respiratory viral infections.